First-Principles Calculations of Two-Dimensional CdO/HfS2 Van der Waals Heterostructure: Direct Z-Scheme Photocatalytic Water Splitting - Zhang, Qiuhua; Ren, Kai; Zheng, Ruxing; Huang, Zhaoming; An, Zongquan; Cui, Zhen (Frontiers in Chemistry, 2022)
Using two-dimensional (2D) heterostructure as photocatalyst for water splitting is a popular strategy for the generation of the hydrogen. In this investigation, the first-principles calculations are explored to address the electronic performances of the 2D CdO/HfS2 heterostructure formed by van der Waals (vdW) forces. The CdO/HfS2 vdW heterostructure has a 1.19 eV indirect bandgap with type-II band alignment. Importantly, the CdO/HfS2 vdW heterostructure possesses intrinsic Z-scheme photocatalytic characteristic for water splitting by obtaining the decent band edge positions. CdO donates 0.017 electrons to the HfS2 layer in the heterostructure, inducing a potential drop to further separate the photogenerated electrons and holes across the interface. The CdO/HfS2 vdW heterostructure also has excellent optical absorption capacity, showing a promising role as photocatalyst to decompose the water.